Structural Variability in Multifunctional Metal Xylenediaminetetraphosphonate Hybrids - Pérez-Colodrero, Rosario Mercedes; Bazaga-García, Montse; Olivera-Pastor, Pascual; Losilla, Enrique R.; Martos, E.Q.; García-Aranda, Miguel Ángel; Cabeza-Díaz, Aurelio (My University, 2013)
The two cornerstones in the field of MOFs are the Secondary Building Units (SBU’s or “bricks”) and the organic linkers. The structural tunability of crystalline MOFs coupled, when possible, with high chemical and thermal robustness, makes them suitable materials to correlate structure with function [1]. Hence, the research focus has been set recently to the potential applications of some of these compounds, including phosphonate-based MOFs [2]. We report two families of isostructural divalent (Ca, Mg, Co, Zn) hybrid phosphonate MOFs based on the tetraphosphonate ligands 1,4- and 1,3-bis(aminomethyl)benzene-N,N’-bis(methylenephosphonic acid), (H2O3PCH2)2-N- CH2C6H4CH2-N(CH2PO3H2)2, (designated as p-C12H20O12N2P4•or m-C12H20O12N2P4, respectively). The use of these two functionalized ligands, otherwise chemically and structurally quite similar, represents a good example of how small stereochemical changes in the organic linker may dramatically affect structural features and dimensionality of the resulting solids and, hence, their final properties. The crystal structures of representative compounds of each family were solved ab initio from synchrotron powder diffraction data (λ=0.2998 Å, beamline ID31-ESRF) and were used as starting models for the Rietveld refinements of the remaining components. M-p-C12H20O12N2P4 (M = Mg, Co and Zn) present low dimensionality (1D) within a wide range of experimental conditions (figure 1). In contrast, solids containing the linker m-H8L, M-m-C12H20O12N2P4 (M = Mg, Ca and Zn) tend to acquire a 3D pillared open-framework for a wide range of metal ion sizes (figure 2). Two representative members, Mg-p-C12H20O12N2P4 and Zn-m-C12H20O12N2P4, were studied for characterizing their proton-conducting behavior. At 98 % RH and T = 297 K, σ are close to 9.4x10-5 Sxcm-1 for both compounds [3]. Their crystal structures, thermal stability and proton conductivity properties will be reported and discussed.
Keywords: Materiales compuestos; Hybrid materials; phosphonates; proton conductivity; X-ray diffraction